Low-field magnetic resonance imaging findings of the caudal portion of the cervical region in clinically normal Doberman Pinschers and Foxhounds - Decker, Steven de; Gielen, Ingrid M.V.L; Duchateau, Luc; Soens, Iris van; Bavegems, Valerie; Bosmans, Tim; Bree, Henri J.J. van; Ham, Luc M.L. van (American journal of veterinary research, 2010)
Objective —To determine the spectrum and frequency of abnormalities for low-field magnetic resonance imaging (MRI) examinations of clinically normal Doberman Pinschers and Foxhounds. Animals —37 clinically normal dogs (20 Doberman Pinschers and 17 Foxhounds). Procedures —For each dog, MRI of the cervical vertebrae (sagittal, dorsal, and transverse T1- and T2-weighted images) was performed. Variables assessed were intervertebral disk degeneration, disk-associated compression, compression of the dorsal portion of the spinal cord, vertebral body abnormalities, and changes in intraparenchymal signal intensity. Associations between these variables and age, breed, sex, and location of the assessed intervertebral disk spaces were evaluated. Results —Severe MRI abnormalities were detected in 17 dogs, including complete disk degeneration (n = 4 dogs), spinal cord compression (3), or both (10). Vertebral body abnormalities were detected in 8 dogs, and hyperintense signal intensity was detected in 2 dogs. Severity of disk degeneration and disk-associated compression was significantly associated with increased age. There was a significant association between disk degeneration, disk-as-sociated compression, and compression of the dorsal aspect of the spinal cord and location of the assessed intervertebral disk space, with the intervertebral disk spaces in the caudal portion of the cervical region being more severely affected. Conclusions and Clinical Relevance —Abnormalities were commonly seen on MRI examinations of the caudal portion of the cervical vertebral column and spinal cord of clinically normal Doberman Pinchers and Foxhounds. Such lesions were probably part of the typical spinal cord degeneration associated with the aging process of dogs.